Talent development in sport: A critical review of pathways to expert performance - Coutinho, P.; Mesquita, I.; Fonseca, A, M. (International Journal of Sports Science & Coaching, 2016)
This review aims to examine the most significant research regarding the development of talent in sport, with a focus on the quantity and type of practice necessary for the attainment of expertise. A total of 54 peer-reviewed empirical articles were collected and analysed for their content. The literature reveals considerable evidence demonstrating that both early specialization and early diversification can lead to expertise development. However, the contrasting views of deliberate practice and deliberate play do not provide a sufficient spectrum of different learning activities for talent development. Furthermore, the content analysis highlights some inconsistencies in the criteria used to characterize different types of learning activities, pointing to the need for a more rigorous and detailed characterization of activities that affect talent development throughout the lifespan. Finally, this review underscores the need for different methodological approaches to complement athletes` perceptions of their past practice experiences gathered from retrospective interviews. The potential value of using systematic observations to provide a detailed examination of the microstructure of different learning activities is discussed.